2012
DOI: 10.1002/wsb.150
|View full text |Cite
|
Sign up to set email alerts
|

Archive eggs: A research and management tool for avian conservation breeding

Abstract: Worldwide, approximately 168 bird species are captive‐bred for reintroduction into the wild. Programs tend to be initiated for species with a high level of endangerment. Depressed hatching success can be a problem for such programs and has been linked to artificial incubation. The need for artificial incubation is driven by the practice of multiclutching to increase egg production or by uncertainty over the incubation abilities of captive birds. There has been little attempt to determine how artificial incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…We have now demonstrated an association between high daily temperatures and decreased daily egg turning during incubation and low hatch success. Therefore, in addition to Smith et al's (2012) recommendations for Whooping Crane artificial incubation protocols to include a dry-bulb temperature of 33-34°C and machine turning of the eggs, to maximize hatching success our results indicate that that daily mean temperatures remain below 33.64°C (the temperature at which 70% of eggs successfully hatch).…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…We have now demonstrated an association between high daily temperatures and decreased daily egg turning during incubation and low hatch success. Therefore, in addition to Smith et al's (2012) recommendations for Whooping Crane artificial incubation protocols to include a dry-bulb temperature of 33-34°C and machine turning of the eggs, to maximize hatching success our results indicate that that daily mean temperatures remain below 33.64°C (the temperature at which 70% of eggs successfully hatch).…”
Section: Discussionmentioning
confidence: 65%
“…An open, and important, question is how the incubation environment affects fitness of hatchlings, as this may have consequences for the success of conservation translocation programmes. Smith et al (2012) suggested that a more successful artificial incubator would incubate at a lower temperature, would have greater variance in temperature, and have a rate of egg turning that allowed for a more even representation of egg positions relative to current models. We have now demonstrated an association between high daily temperatures and decreased daily egg turning during incubation and low hatch success.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations